THE ROLE OF EDUCATORS IN ENHANCING LITERACY SKILLS AMONG ELEMENTARY SCHOOL STUDENTS: UTILIZING MULTIMODAL TEXTS - Awanda, Ifan; Sari, Tri Maya; Susilowati, Ayu Rizki (STIT Pringsewu, 2025)
Abstract This research aims to understand the important role of teachers in improving literacy skills among students through effective teaching and support by involving multimodal literacy. The method in this study uses a qualitative approach with library research. The result of this research is that by applying various teaching strategies that align with different learning styles and abilities, teachers play a role that can enhance literacy skills with multimodal texts, thereby creating a more inclusive and engaging learning environment for students. This emphasizes the importance of integrating multimodal literacy teaching in elementary schools to better prepare students for the digital era. Keywords: Literacy skills, Multimodal texts. Teaching strategies.